Visualisasi Dan Monitoring Data Akreditasi Terintegrasi Berbasis Web Di Politeknik Negeri Media Kreatif - AGUS WIRANTO; Dhiya Alfiyyah Ansar; Hadi Rudiya; Rezki Aulia; Muhammad Hafif Yadi; Doni El Rezen Purba (Teknik Komputer Politeknik Negeri Sriwijaya, 2026)
This study presents the development of the Accreditation Data Fulfillment Support Information System (SIPDAK) at Politeknik Negeri Media Kreatif using a User-Centered Design approach. The system integrates accreditation data from multiple work units into a single unified database (“one data”), enabling efficient monitoring of document validity and management. The interactive dashboard includes the “Upcoming Accreditation Expiry” widget, urgency badges, and an animated character to improve readability and user awareness. Implementation results indicate increased efficiency in data management, clear visualization of accreditation urgency, and enhanced monitoring capabilities for staff and administrators. These outcomes are important for ensuring institutional readiness for accreditation evaluation, facilitating timely decision-making, and reducing the risk of delayed documentation. Keywords— Integrated Information System, Accreditation Monitoring, Interactive Dashboard, SIPDAK, User-Centered Design